2020
DOI: 10.3390/f11121359
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal and Leaf Morphology Response of European Beech (Fagus sylvatica L.) Provenances Transferred to Contrasting Climatic Conditions

Abstract: Climate change-induced elevated temperatures and drought are considered to be serious threats to forest ecosystems worldwide, negatively affecting tree growth and viability. We studied nine European beech (Fagus sylvatica L.) provenances located in two provenance trial plots with contrasting climates in Central Europe. Stomata play a vital role in the water balance of plants by regulating gaseous exchanges between plants and the atmosphere. Therefore, to explain the possible adaptation and acclimation of prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 106 publications
(149 reference statements)
3
19
0
Order By: Relevance
“…These traits include stomatal number in leaves and stem anatomical traits. When watering occurred less frequently, seedlings belonging to the Evros population had a significantly lower density of stomata on their leaves, which is a typical response of beech populations when transferred to drier and warmer climates [ 32 ]. The same treatment caused the opposite trend in seedlings from Drama, which thus had increased stomatal density on their leaves when watering occurred less frequently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These traits include stomatal number in leaves and stem anatomical traits. When watering occurred less frequently, seedlings belonging to the Evros population had a significantly lower density of stomata on their leaves, which is a typical response of beech populations when transferred to drier and warmer climates [ 32 ]. The same treatment caused the opposite trend in seedlings from Drama, which thus had increased stomatal density on their leaves when watering occurred less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Plants experiencing prolonged drought intervals between precipitation events usually respond directly to environmental stress by modifying various aspects of their phenology, physiology, morphology and/or anatomy [ 18 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Additionally, plant populations originating from different locations often appear to modify stomata parameters such as size or density, as a result of adaptation to the varying levels of precipitation on their original site [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasion success may be influenced by phenotypic plasticity and the evolution of reproductive characteristics, which are related to the seeds’ polymorphism and their dispersal behavior [ 61 ]. Accordingly, these features are required for invasive plants because they are related to dispersal tactics and systems to cope with environmental stress, maximizing their performance and establishment in the new environment [ 55 , 62 ]. This could also be related to the susceptibility of seeds to the various abiotic and biotic conditions [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on survival rates, morphological, and physiological features, they concluded that Quercus pubescens may be a suitable candidate forest tree for poor and dry soils under the expected summer heat and drought conditions in Central Europe. In the same context, a provenance trials approach was used to evaluate nine European beech (Fagus sylvatica L.) provenances under contrasting climates [6]. An acclimation potential of provenances transferred to warmer and drier conditions was indicated by the development of smaller leaves with decreasing stomatal density and length of guard cells.…”
Section: Tree Adaptive Responses To Climatic Variabilitymentioning
confidence: 99%